Comparison of haemoglobin assessment by HemoCue 301 and automated haematology analyser using flowcytometry among school going children: a one year study at a tertiary care hospital - Kumar, Sarvepalli Vijaya; Ramalingam, Krishnan (International Journal of Research in Medical Sciences, 2019)
Background: Anaemia defined as reduction in the concentration in Haemoglobin is one of the key health indicators of health care system of the country. Accurate screening methods are required to estimate the levels of haemoglobin for diagnosing the cause of anaemia. Objectives of the study was to analyze and compare the results of haemoglobin concentrations estimated with automated haematology analyzer and point of care device HemoCue Hb301. Methods: It is a prospective cross-sectional study was conducted for one year after ethical approval. Non fasting capillary and venous blood samples were collected from the selected cases of children and Haemoglobin concentrations were estimated by automated analyzer and HemoCue Hb301 system and the values were noted. Quality control checks were performed for both. Statistical analysis was done using IBM SPSS Version 24.0. Results: Mean Hb% concentration was estimated in 108 children with 44 female and 64 males. The mean value of Automated hematology analyzer (11.965±1.012) was significantly higher when compared with the mean value of HemoCue Hb301 (11.697±1.312) (p=0.002). There was a significantly strong correlation between HemoCue Hb301and Automated hematology analyzer (r-value = 0.732, p <0.0001). Conclusions: The HemoCue is useful in many different settings and remains a widely used method in field settings as it has several advantages and is relatively inexpensive compared with automated haematology analysers. Further studies are needed to better understand potential sources of error in the Hb assessment by HemoCue with the aim to better train phlebotomists and implement appropriate standardised procedures.